Meta Analisis Bioetika terhadap Aborsi Perspektif Moral dan Medis - Mulia, Elsa; Syamsurizal, S. (Jurnal Biologi Babasal, 2024)
This study addresses the controversial issue of abortion and applies bioethical analysis to understand its moral and medical implications. In the social and cultural context, abortion raises ethical questions about the right to life, women's well-being, and bodily autonomy. Despite regulations in the Indonesian Health Law, the implementation of abortion remains controversial. The research methodology employs the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA), analyzing five selected articles from Google Scholar. The findings provide a comprehensive overview of abortion in the contexts of religion, bioethics, law, and psychology. Confronting ethical debates on abortion, this study emphasizes the balance between women's rights, ethical values, and legal considerations as crucial elements. Awareness of diverse perspectives and values in the abortion issue is essential for inclusive and fair policy-making, contributing to a profound understanding and holistic policy development in the field of education.